Breaking biases and building momentum for transforming agricultural research for development practices: recommendations and research opportunities - McGuire, Erin; Ewell, Hanna; Bailey, Arwen; Leñero, Eva Marina Valencia; Luu, Thi Thu Giang; Sylvester, Janelle Marie; Al-Zu’bi, Maha; Liani, Millicent L.; Kabirigi, Michel (2025)
Ongoing food system inequalities and pressures on planetary boundaries requires a paradigm shift among agricultural research for development (AR4D) actors to produce effective innovation for sustainable environmental and social outcomes. Building on insights from Agricultural Innovation System literature and recognizing the influence of personal and systemic biases within AR4D, the following recommendations address upstream challenges, interdisciplinary collaboration, emphasize outcome-driven scaling, adaptive project implementation, and integrate critical considerations for social differentiation.